Realizing The Religion As The Source Of Harmony In A Multicultural Society - Izzuddin Izzuddin; Ahmad Khoirul Fata (IAIN Tulungagung, 2020)
Abstract This paper examines the potential of religion as the main source of harmony in a plural society. This paper itself is motivated by the fact that religion has two different faces: integrative and confrontational. On the one hand religion can encourage integration in society, however religion also has the potential to cause conflict and tension in the community, especially in the people with complex levels of diversity. In multicultural societies, integrative religious attitudes are needed to avoid conflicts. But making it happen is not as easy as turning our hand. The factor of understanding religious texts that are exclusive and based on hatred is one of the challenges. This will be further complicated when external factors (economic, political) are involved. By using philosophical-reflective methods, the writer offers two ways of religious that can create harmony in different cultures and beliefs, namely: exclusivenes-tolerance religious, and willingness to engage in interfaith dialogue. With these two things the writer believes that religious people still feel comfortable with the truth of their own religion, and at the same time they live in peace with people of different religions. Keywords: Diversity, Conflict, Multicultural Society, Exclusive-Tolerant, interfaith Dialogue. Abstrak Tulisan ini mengkaji tentang potensi agama sebagai sumber utama harmoni dalam masyarakat majemuk. Tulisan ini sendiri dilatar belakangi oleh kenyataan bahwa agama memiliki dua wajah yang saling berbeda: integratif dan konfrontatif. Di satu sisi agama bisa mendorong terjadinya integrasi dalam masyarakat, namun demikian agama juga berpotensi menimbulkan konflik dan ketegangan di tengah masyarakat, khususnya masyarakat dengan tingkat keragaman yang kompleks.Dalam masyarakat multikultural, sikap beragama yang integratif sangat diperlukan agar tidak terjadi konflik. Namun mewujudkannya tidak semudah membalikkan tangan. Faktor pemahaman terhadap teks-teks keagamaan yang tertutup dan didasari kebencian menjadi salah satu tantangan. Ini akan semakin rumit ketika faktor-faktor eksternal (ekonomi, politik) turut terlibat. Dengan menggunakan metode filosofis-reflektif penulis menawarkan dua cara beragama yang bisa mewujudkan harmoni dalam masyarakat yang berbeda budaya dan keyakinan, yaitu: keberagamaan yang ekslusif-toleran, dan kesediaan diri untuk melakukan dialog antarumat beragama. Dengan dua hal ini penulis meyakini umat beragama tetap merasa nyaman dengan kebenaran agamanya sendiri, dan di saat bersamaan mereka hidup damai dengan umat agama yang berbeda. Kata Kunci : Keberagamaan, Konflik, Masyarakat Multikultural, Ekslusif-Toleran, Dialog Antaragama.